Perlindungan Hukum Bagi Dokter Gigi Praktisi Teledentistry Dalam Menghadapi Risiko Alergi Obat - Lisa Lamusul Afiyah; Sigit Irianto (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2024)
Teledentistry is a relatively new combination of telecommunications technology and dental care. It has its roots in telemedicine, which involves the use of communications and information technology to provide health services across geographic distances. Teledentistry faces several challenges, including limited internet access and inadequate infrastructure in remote areas, concerns about the confidentiality of electronic medical records, and incomplete regulations regarding teledentistry in the current law. The problems raised in this research are the obstacles faced by teledentistry practitioners in Indonesia, including factors that hinder their ability to manage medical risks and legal protection for teledentistry practitioners who face medical risks such as drug allergies. Legal protection for dentists in the field of teledentistry when facing medical risks, such as allergies to electronically prescribed medications. Dentists must obtain legal guarantees and certainty in providing health services to their patients. The conclusion of this study is that in teledentistry consultation services, medical risks such as drug allergies, which are unpredictable reactions of the patient's body, cannot be predicted. Medical risk is not a form of medical malpractice. Because, in medical risks, one of the elements in articles 338 and 359 of the Criminal Code cannot be fulfilled, namely the element of negligence.